Design of Vitex Negundo Nanoemulsion for Anti-Inflammatory Activity Targeting Anal Fissure - Gupta, Jitendra (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: The aim of this study was to design and characterize a topical nanoemulsion of Nirgundi oil for the treatment of anal fissures and to evaluate its in-vitro anti-inflammatory activity and in-vivo anal fissure healing potential. Materials and Methods: A pseudo-ternary phase diagram was constructed to determine the Northeast region suitable for nanoemulsion formation. Based on this, six different batches of nanoemulsion were prepared. These formulations were characterized for globule size and surface morphology, refractive index, zeta potential, pH, viscosity, drug-excipient compatibility, drug entrapment and loading efficiency, thermodynamic stability, and in-vitro drug permeation. From the six batches, B6 was selected as the best formulation and subjected to further in-vitro anti-inflammatory testing using the egg albumin denaturation and COX-II enzyme inhibition assay. Additionally, in-vivo anal fissure healing activity was assessed using histological analysis of tissue samples. Results and Discussion: The B6 formulation demonstrated significant in-vitro anti-inflammatory activity, with 91.17% suppression in the egg albumin denaturation assay compared to 79.38% for the reference drug (diclofenac). The COX-II inhibition assay revealed an IC₅₀ of 3.735 μg/mL for B6, which was more effective than the marker sabinene (IC₅₀: 6.594 μg/mL). In-vivo studies confirmed that the B6 formulation showed significant improvement and healing of anal fissures, indicating successful therapeutic action. These results suggest that the nanoemulsion enhances the bioavailability and therapeutic efficacy of Nirgundi oil for local treatment. Conclusion: The study finally concluded that the topical nanoemulsion formulation of Nirgundi oil (B6) has potent anti-inflammatory action and effectively promotes healing in anal fissures. It showed significant therapeutic potential and can be considered a promising candidate for further development as a topical treatment for anal fissures.